2004
DOI: 10.1007/978-3-540-24595-7_41
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Graph Drawing: Layout Algorithms and Visualization Schemes

Abstract: Abstract. In this paper we consider the problem of drawing and displaying a series of related graphs, i.e., graphs that share all, or parts of the same vertex set. We designed and implemented three different algorithms for simultaneous graph drawing and three different visualization schemes. The algorithms are based on a modification of the force-directed algorithm that allows us to take into account vertex weights and edge weights in order to achieve mental map preservation while obtaining individually readab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…Given that Erten et al [8] had shown the superiority of a combined node-link view over separate node-link views for multiple graphs, we decided to investigate whether the same held true for the other main visualization method for graphs -the matrix. Thus, our aim was to determine whether a combined matrix would prove superior both in terms of user preference and of performance when compared to juxtaposed matrices.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that Erten et al [8] had shown the superiority of a combined node-link view over separate node-link views for multiple graphs, we decided to investigate whether the same held true for the other main visualization method for graphs -the matrix. Thus, our aim was to determine whether a combined matrix would prove superior both in terms of user preference and of performance when compared to juxtaposed matrices.…”
Section: Previous Workmentioning
confidence: 99%
“…Erten et al's [8] work in particular concluded that for collections of small graphs shown as node-link views, a combined view was superior to a juxtaposition of separate graph views for discovering similarities and differences between the set of graphs. Meanwhile, Beck and Diehl's recent work [18] showed the relations within and between multiple revisions of source code, combined into a single matrix view.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Erten et al . [EKLN04], in contrast, allow the same node to have different positions on the layers; to preserve the mental map, they use an adapted force‐directed layout algorithm that moves the same nodes to at least similar positions across layers (Figure , relaxed positions). Groh et al .…”
Section: Taxonomy and Classification Of Dynamic Graph Visualization Tmentioning
confidence: 99%
“…Similarly, Brandes and Corman [BC03] depict nodes as cylinders, but also add transparent planes that help discern the stacked layers (Figure 8, fixed positions). Erten et al [EKLN04], in contrast, allow the same node to have different positions on the layers; to preserve the mental map, they use an adapted force-directed layout algorithm that moves the same nodes to at least similar positions across layers (Figure 8, relaxed positions). Groh et al [GHW09] extend this approach by abstracting from nodes and links: they just use the connections between the same nodes of different layers (i.e.…”
Section: Iia Node-link-based Approachesmentioning
confidence: 99%